Low Homoarginine Levels in the Prognosis of Patients With Acute Chest Pain - Atzler, Dorothee (J Am Heart Assoc, 2016)
BACKGROUND: The endogenous amino acid homoarginine predicts mortality in cerebro‐ and cardiovascular disease. The objective was to explore whether homoarginine is associated with atrial fibrillation (AF) and outcome in patients with acute chest pain. METHODS AND RESULTS: One thousand six hundred forty‐nine patients with acute chest pain were consecutively enrolled in this study, of whom 589 were diagnosed acute coronary syndrome (ACS). On admission, plasma concentrations of homoarginine as well as brain natriuretic peptide (BNP), and high‐sensitivity assayed troponin I (hsTnI) were determined along with electrocardiography (ECG) variables. During a median follow‐up of 183 days, 60 major adverse cardiovascular events (MACEs; 3.8%), including all‐cause death, myocardial infarction, or stroke, were registered in the overall study population and 43 MACEs (7.5%) in the ACS subgroup. Adjusted multivariable Cox regression analyses revealed that an increase of 1 SD of plasma log‐transformed homoarginine (0.37) was associated with a hazard reduction of 26% (hazard ratio [HR], 0.74; 95% CI, 0.57–0.96) for incident MACE and likewise of 35% (HR, 0.65; 95% CI, 0.49–0.88) in ACS patients. In Kaplan–Meier survival curves, homoarginine was predictive for patients with high‐sensitivity assayed troponin I (hsTnI) above 27 ng/L (P<0.05). Last, homoarginine was inversely associated with QTc duration (P<0.001) and prevalent AF (OR, 0.83; 95% CI, 0.71–0.95). CONCLUSION: Low plasma homoarginine was identified as a risk marker for incident MACEs in patients with acute chest pain, in particular, in those with elevated hsTnI. Impaired homoarginine was associated with prevalent AF. Further studies are needed to investigate the link to AF and evaluate homoarginine as a therapeutic option for these patients.